Impact of ionic liquid on structural, thermal and transport properties in gellan gum-lithium triflate solid polymer electrolyte - Arifin, K.H.; Osman, Z.; Tamchek, N.; Ghazali, M.I.M.; Noor, I.M. (Elsevier, 2023)
60 wt% gellan gum (GG) complexes with 40 wt% lithium trifluoromethanesulfonate (LiTf) solid polymer electrolytes (SPEs) with different concentrations of ethyl-dimethyl-propylammonium bis(tri-fluoromethylsulfonyl)imide, [EDPA][TFSI] ionic liquid (IL) have been prepared by solution casting technique. The aim of this work is to investigate the impact of IL in GG-LiTF SPEs on electrical, structural and thermal properties. The room temperature conductivity of 0.54 mS cm−1 has been obtained for the free IL sample. Addition of IL up to 20 wt% increases the conductivity to 2.18 mS cm−1. The contributing factors in the increase of conductivity were studied based on its structural characterisations. The addition of IL up to 20 wt% into the SPE has reduced the crystallinity nature to become more amorphous as can be seen in XRD deconvolution and DSC analysis. This change in structural nature has created more space between the polymer matrix for the free ions to dissociate and drive through the SPE, hence increasing conductivity. Nevertheless, the IL added seems not to affect the dissociation ratios of free ions, ion pairs and ion aggregates of LiTf, despite of clear complexation that occurred between GG and both ionic salts from FTIR analysis. Thus, the conductivity trend is governed by both charge carriers’ mobility and concentration in the electrolyte which can also be seen at elevated temperatures.